Case Report: Improvement Following Immunotherapy in an Individual With Seronegative Down Syndrome Disintegrative Disorder - Hart, Sarah J.; Worley, Gordon; Kishnani, Priya S.; Van Mater, Heather (Frontiers in Neurology, 2021)
Down syndrome disintegrative disorder (DSDD) is a condition of unknown etiology characterized by acute cognitive decline, catatonia, insomnia, and autistic features in individuals with Down syndrome. A prior report of four patients with DSDD suggested a potential autoimmune etiology based on the presence of autoantibodies and on successful treatment with immunotherapy that included intravenous immunoglobulin (IVIG). Herein, we present the case of an 8-year old girl who developed acute cognitive decline to a dementia-like state, insomnia, catatonia, and autistic features. In contrast to the four patients with DSDD above, she had no evidence of autoimmunity and presented at a younger age. Given the gravity of her acute deterioration and the exclusion of other etiologies, she was treated with immunotherapy presumptively. She responded with near complete resolution of symptoms, but demonstrated a pattern of mild decline as she approached each monthly dosing of IVIG and steroids, reversed by treatment. Mycophenolate mofetil (MMF) was therefore added, with stability throughout the month and the ability to taper off IVIG. After stopping IVIG, she had a mild recurrence of symptoms that again resolved with repeat IVIG followed by tapering off. Outcome was assessed at 2.5 years after presentation, at which time she was back to her premorbid condition, except for persistent tics off immunotherapy. This case supports the contention that patients with a rapid onset of severe symptoms consistent with DSDD, who have a thorough evaluation with the exclusion of other etiologies, may warrant a trial of immunotherapy with steroids, IVIG and/or other agents like MMF even in the absence of evidence of autoimmunity on standard evaluation.